Theoretical investigation on PD-L1-In-1 for cancer immunotherapy via density functional theory - Bijay Sijapati Magar; Kiran Pudasainee; Prakash Pandey; Mahesh Kumar Neupane; Rupak Raj Lamichhane; Basanta Gurung; Khagendra Tripathi; Binod Adhikari (Scientific Reports)
Abstract This study presents a comprehensive theoretical analysis of PD-L1-In-1 (C21H23N5O2) using the B3LYP functional with the 6-311G(d) basis set, focusing on its structural, electronic, and spectroscopic properties. Fourier Transform Infrared (FT-IR), Raman, and UV–Vis spectra were simulated, and vibrational modes were assigned via potential energy distribution (PED) analysis using the VEDA 4 program. Natural Bond Orbital (NBO) analysis revealed hyperconjugative interactions (E 2) and provided insights into donor–acceptor electron densities. The energy band gap was obtained from HOMO–LUMO calculations and further analyzed through the density of states (DOS) spectrum. Electron Localization Function (ELF) and Localized Orbital Locator (LOL) analyses, performed using Multiwfn, highlighted regions of electron localization and orbital overlap. Reduced Density Gradient (RDG) analysis uncovered non-covalent interactions. Ground-state 1H and 13C NMR chemical shifts were predicted using the Gauge-Independent Atomic Orbital (GIAO) method. Fukui function analysis identified reactive sites and evaluated the chemical reactivity of the molecule. Molecular docking studies using AutoDock Vina explored interactions between PD-L1-In-1 and the PD-L1 checkpoint protein, shedding light on its potential biological activity. Notably, the simulations indicated strong ligand–protein interactions, positioning PD-L1-In-1 as a promising candidate for cancer immunotherapy targeting the PD-1/PD-L1 pathway.